A global pollutant (PVC-polyvinyl chloride) applied as heavy metal binder from aqueous samples: green principles from synthesis to application - Silva, Adrielli C. P. [UNESP]; Jorgetto, Alexandre O. [UNESP]; Wondracek, Marcos H. P. [UNESP]; Saeki, Margarida J. [UNESP]; Pedrosa, Valber A. [UNESP]; Colmenares, Yormary N.; Mastelaro, Valmor R.; Sutili, Felipe K. [UNESP]; Martines, Marco A. U.; Pasta, Paula C. [UNESP]; Castro, Gustavo R [UNESP] (Taylor & Francis, 2021)
We have developed a clean route for the modification of polyvinylchloride surface (PVC) with 4-amino-5-hydrazino-1,2,4-triazole-3-thiol molecule. The modification reaction was investigated through Fourier Transform Infrared Spectroscopy (FTIR) and X-ray Photoelectron Spectroscopy (XPS) analysis. According to our findings, S-H groups are responsible to the molecule attachment and nitrogen atoms are directly involved in metal ion coordination. These results are in agreement with the pseudo-second-order kinetic model, which infers that chemisorption is the main mechanism for metal removal. Adsorption isotherms of Cd(II), Cu(II) and Pb(II) follow the Langmuir model and the results indicated that Ns values are 0.39, 0.52 and 0.15 mmol g−1, respectively. The calculated Ømax values for Cu(II), Pb(II) and Cd(II) were 3.93, 2.95 and 1.13, respectively, indicating that three types of complex are formed depending on the adsorbed species. Therefore, it can be concluded that PVC use as adsorbent is feasible since it requires a simple modification reaction with nontoxic and low-cost solvents.
Keywords: clean step reaction; Heavy metal removal; hydrophobicity; surface characterization